High-performance liquid-solid self-powered sensing component and manufacturing method thereof

By replicating the lotus leaf mastoid structure on the surface of the friction layer and alkalizing it, combined with liquid metal assembly, the problems of improving the electrical performance and service life of the existing liquid-solid friction nanogenerator are solved, and high-performance output and good stability and durability are achieved.

CN119765983APending Publication Date: 2025-04-04GUANGDONG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411945060.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

There is room for improvement in the electrical performance and service life of existing liquid-solid friction nanogenerators, and the construction of a single surface microstructure cannot achieve a significant increase in output performance.

Method used

The mastoid structure on the surface of the lotus leaf is replicated on the surface of the friction layer and alkalized. Combined with liquid metal assembly, the surface charge is enhanced to improve performance output.

Benefits of technology

It significantly improves the electrical performance of liquid-solid friction nanogenerators, with an increase of open circuit voltage and short circuit current by about 2.8 times, while improving the stability and durability of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119765983A_ABST
    Figure CN119765983A_ABST
Patent Text Reader

Abstract

The invention discloses a high-performance liquid-solid type self-powered sensing component. A mastoid structure with a lotus leaf surface is re-carved on the surface of a friction layer, alkalization treatment is performed on the surface on the basis of the mastoid structure, and then the mastoid structure and liquid metal are assembled together, so that the surface charge quantity is increased, the performance output is improved, and the stability and durability are high. According to the technical scheme, the device comprises an upper-layer component and a lower-layer component, wherein each of the upper-layer component and the lower-layer component comprises a substrate, a solid friction layer, liquid metal, a gasket and a wire connected with an external circuit; the solid friction layer is a polydimethylsiloxane film with a lotus leaf microstructure; the substrate is a polydimethylsiloxane thin film; the gasket is a polydimethylsiloxane film with a hollow center; the liquid metal is used as a liquid friction layer and an electrode; belongs to the technical field of electric sensing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electric sensing technology, and in particular to a high-performance liquid-solid self-powered sensing component and a manufacturing method thereof. Background Art

[0002] Triboelectric nanogenerator (TENG) is a device for efficiently collecting environmental mechanical energy first proposed by Academician Wang Zhonglin in 2012. Its power generation principle is the coupling effect of friction electrification and electrostatic induction. The positive and negative friction layers of the triboelectric nanogenerator will continuously generate current during the relative motion, so the mechanical signal can be directly converted into an electrical signal to achieve self-powered sensing. Therefore, the triboelectric nanogenerator can be used to prepare pressure sensors for hand grasping tests, which can convert mechanical energy generated by finger movement or bending into electrical energy, and transmit the grasping condition data to the system to achieve self-powered grip data transmission. The system can provide more accurate and personalized treatment plans based on the transmitted data. Because its self-powered feature does not require external charging, and its small size is easy to carry, it can also be used for daily monitoring of patients' grasping conditions and assist in patients' treatment.

[0003] According to the morphology of the friction layer material, the friction nanogenerator can be mainly divided into solid-solid friction nanogenerator and liquid-solid friction nanogenerator. Solid-solid friction nanogenerator is easily affected by the external environment. At the same time, long-term operation will cause the loss of solid friction layer materials and reduce the service life; while the fluidity of the liquid makes the solid-liquid interface contact more closely, with a larger contact area, and almost no loss of solid materials. The larger the contact area between the friction layer materials, the better the triboelectric performance of the friction nanogenerator. In order to increase the contact area, many scholars have made microstructures on the surface of the friction nanogenerator material, such as sandpaper, stripes, pyramid structures, etc.

[0004] However, the increase in electrical performance of a single surface microstructure is small and cannot achieve a significant increase in its output performance. Therefore, it is necessary to develop a suitable method to increase the electrical performance of the liquid-solid friction nanogenerator while increasing its service life. Summary of the invention

[0005] The present invention proposes a high-performance liquid-solid self-powered sensor component, which replicates the papillary structure of the lotus leaf surface on the surface of its friction layer, and on this basis, the surface is alkalized and finally assembled with liquid metal to increase its surface charge and thus improve performance output, and has strong stability and durability.

[0006] The second object of the present invention is to provide a method for manufacturing the high-performance liquid-solid self-powered sensor component, which has the advantages of being simple, mass-producible, low-cost, and green and environmentally friendly.

[0007] To this end, the first technical solution provided by the present invention is as follows:

[0008] A high-performance liquid-solid self-powered sensor component comprises an upper component and a lower component, wherein the upper component and the lower component both comprise a substrate, a solid friction layer, a liquid metal, a gasket, and a wire connected to an external circuit;

[0009] The solid friction layer is a polydimethylsiloxane film with a lotus leaf microstructure;

[0010] The substrate is a polydimethylsiloxane film;

[0011] The gasket is a polydimethylsiloxane film with a hollow center;

[0012] The liquid metal serves as a liquid friction layer and an electrode.

[0013] Furthermore, in the above-mentioned high-performance liquid-solid self-powered sensor component, a heightening gasket is provided between the upper component and the lower component, and the heightening gasket is a polydimethylsiloxane film with a hollow center.

[0014] In this case, the mass ratio of all polydimethylsiloxane and liquid metal in the high-performance liquid-solid self-powered sensor element is 2.325-3.425:1.204-3.606; preferably 2.325:2.404.

[0015] Furthermore, in the above-mentioned high-performance liquid-solid self-powered sensor component, the liquid metal is eutectic gallium indium.

[0016] Furthermore, in the above-mentioned high-performance liquid-solid self-powered sensor component, the polydimethylsiloxane is Dow Corning 184PDMS.

[0017] Furthermore, in the above-mentioned high-performance liquid-solid self-powered sensor component, the solid friction layer is prepared by the following method: the microstructure of the surface of a fresh lotus leaf is replicated by the yin-yang molding method to obtain a polydimethylsiloxane film with a lotus leaf microstructure, the surface of the film is alkalized, and then the polydimethylsiloxane film with a lotus leaf microstructure is obtained after cleaning and drying, which is the solid friction layer.

[0018] Furthermore, the negative mold of the above-mentioned high-performance liquid-solid self-powered sensor component is prepared by the following method: vacuum degassing polydimethylsiloxane is poured into a plastic dish with a diameter of a lotus leaf, vacuuming it again, putting it in an oven for drying, and then peeling off the lotus leaf to obtain the negative mold.

[0019] More specifically, the negative mold is prepared by the following method: 13.2 g of Dow Corning 184PDMS is vacuum degassed for 20-30 minutes and then poured into a plastic dish with a diameter of 60 mm containing lotus leaves, and then vacuumed again for 20-30 minutes, placed in a 60-80°C oven, and dried for 2-4 hours. After drying, the lotus leaf blades are peeled off to obtain the negative mold.

[0020] Furthermore, for the high-performance liquid-solid self-powered sensor component described above, the specific operation of the positive mold is as follows: an anti-adhesion layer is formed on the surface of the negative mold, polydimethylsiloxane is evenly spin-coated on the anti-adhesion layer of the negative mold again, and the mold is placed in a 60-80°C oven for drying for 2-4 hours. The dried upper film is peeled off from the surface of the negative mold to obtain the positive film with a lotus leaf microstructure.

[0021] More specifically, the specific operation of the positive mold is as follows: the negative mold is placed in a plastic dish with a lid, and then 100 μL of chlorotrimethylsilane is dripped into the dish, and the lid of the plastic dish is immediately covered. The lid is opened after 1-2 minutes, and the chlorotrimethylsilane is completely evaporated at room temperature to form an anti-adhesion layer on the surface of the negative mold. Again, 4.4 g of Dow Corning 184PDMS is evenly spin-coated on the anti-adhesion layer of the negative mold using a gel spreader at a speed of 500 rpm, and then placed in a 60-80°C oven for drying for 2-4 hours. The dried upper film is peeled off from the surface of the negative mold to obtain a positive film with a lotus leaf microstructure.

[0022] Furthermore, for the above-mentioned high-performance liquid-solid self-powered sensor component, the method for alkalizing the surface of the positive mold with lotus leaf microstructure is: exposing the positive mold with lotus leaf microstructure to an ultraviolet ozone environment for 40 minutes to 1 hour, and then quickly spraying 1M NaOH solution on its surface, letting it stand for more than 1 hour, and drying the solution residue on its surface.

[0023] The second technical solution of the present invention is to provide a method for manufacturing the above-mentioned high-performance liquid-solid self-powered sensor component, which comprises the following steps in sequence:

[0024] 1) Making upper components and lower components, the upper components and lower components are made by the same method, which is as follows:

[0025] After vacuum degassing, polydimethylsiloxane is evenly spin-coated on a glass sheet carrier as a substrate. After the substrate is heated to a semi-cured state, a solid friction layer and a hollow polydimethylsiloxane gasket are sequentially placed on the surface of the substrate from bottom to top, so that the solid friction layer is combined with the substrate and the hollow polydimethylsiloxane gasket, and then dried at 60-80° C. for standby use;

[0026] 2) Combine the polydimethylsiloxane gaskets of the upper and lower components, use polydimethylsiloxane to bond the joint, then inject liquid metal into the middle hollow part, lead out the wire from the injection port for connection with the external circuit, and finally use polydimethylsiloxane to seal the hole.

[0027] More specifically:

[0028] 1) Making upper components and lower components, the upper components and lower components are made by the same method, which is as follows:

[0029] After degassing Dow Corning 184PDMS in vacuum, use a coating machine at 500 rpm to evenly spin-coat it on a glass sheet as a substrate. After the substrate is heated to a semi-cured state, an alkalized positive mold and a PDMS gasket are placed on the surface of the substrate from bottom to top, so that the alkalized positive mold is combined with the substrate and the PDMS gasket, and then dried at 60-80°C until it is completely cured;

[0030] 2) Combine the polydimethylsiloxane gaskets of the upper and lower components, use polydimethylsiloxane to bond the joints, then inject 0.4 mL of liquid metal into the middle hollow part, lead out a 2-3 cm long copper wire from the injection port for connection with the external circuit, and finally use polydimethylsiloxane to seal the hole.

[0031] Furthermore, in the above-mentioned method for manufacturing a high-performance liquid-solid self-powered sensor component, the polydimethylsiloxane gasket is prepared by the following method:

[0032] 1) After vacuum degassing, evenly spin-coat the polydimethylsiloxane on a glass sheet and dry it;

[0033] 2) Repeat step 1) and then slice to obtain a polydimethylsiloxane gasket.

[0034] More specifically: the polydimethylsiloxane gasket is prepared by the following method:

[0035] 1) After vacuum degassing, 4.4 g of Dow Corning 184 PDMS was evenly spin-coated on a 60 mm x 60 mm glass sheet at 500 rpm using a coating machine, and then placed on a heating table at 80° C. for drying for 1 h;

[0036] 2) Repeat step 1) and then slice to obtain a PDMS gasket.

[0037] Compared with the prior art, the technical solution provided by the present invention has the following technical advantages:

[0038] (1) The friction layer surface of the technical solution provided by the present invention replicates the papillary structure of the lotus leaf surface. The bionic lotus leaf microstructure on the surface of the solid friction layer can enhance the hydrophobicity of polydimethylsiloxane and effectively improve the wettability of liquid metal on the polydimethylsiloxane surface. On this basis, the surface is alkalized to increase its surface charge and thus improve performance output.

[0039] (2) The technical solution provided by the present invention adopts a self-powered sensor device prepared by effectively combining the bionic lotus leaf microstructure with the surface alkalinization modification, which greatly improves the performance output of the self-powered sensor device. The open circuit voltage and short circuit current of the device are improved by about 2.8 times in terms of electrical performance compared with the self-powered sensor components without any treatment. It has been proved to have good stability and durability through long-term impact, multiple stretching and torsion tests.

[0040] (3) The technical solution provided by the present invention is composed of a solid friction layer, a polydimethylsiloxane base, liquid metal, and a polydimethylsiloxane gasket. In the working state, the contact separation distance can change the height of the gasket according to the needs of the application scenario; the liquid metal not only has excellent conductivity, but also can improve the triboelectric performance as a liquid friction layer; at the same time, the amorphous and flowable characteristics of the liquid metal make it highly flexible, able to quickly adjust its own shape, and have a fast response speed; the lead wires are used for data collection and are applied to human motion energy collection and human motion monitoring.

[0041] (4) The technical solution provided by the present invention has the advantages of simple production method, mass production, low cost, and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 It is a schematic diagram of the structure of a high-performance liquid-solid self-powered sensor component;

[0043] Figure 2 The scanning electron microscope images of different solid friction layers;

[0044] Among them, (a) is an electron micrograph of the surface of a fresh lotus leaf; (b) is an electron micrograph of a negative mold, (c) is an electron micrograph of a positive mold, (d) is an electron micrograph after ultraviolet ozone irradiation, and (e) is an electron micrograph of the solid friction layer provided in Example 1;

[0045] Figure 3 The diagram of water contact angle variation of different solid friction layers;

[0046] Wherein: (a) is the water contact angle of the solid friction layer without any treatment, (b) is the water contact angle of the solid friction layer with a single bionic lotus leaf microstructure, and (c) is the water contact angle of the solid friction layer provided in Example 1;

[0047] Figure 4This is a comparison chart of the anti-sticking performance of different solid friction layers on liquid metal;

[0048] Among them: (a) is a solid friction layer without any treatment, (b) is a solid friction layer with a single bionic lotus leaf microstructure,

[0049] Figure 5 Comparison chart of the open circuit voltage, short circuit current and transferred charge amount in the triboelectric performance test;

[0050] Among them: (a) is the comparison result of the open circuit voltage of different TENGs; (b) is the comparison result of the short circuit current of different TENGs; (c) is the comparison result of the transferred charge of different TENGs.

[0051] Figure 6 This is the stability and durability test diagram of the sensor;

[0052] Among them: (a) is the stability test result after multiple twisting, stretching and folding; (b) is the durability test result after 2000 cycles of impact; the sensor exhibits excellent long-term stability and durability.

[0053] Figure 7 In order to apply it to the collection of human motion energy, (a) is the circuit connection diagram, (b) is the actual diagram;

[0054] Figure 8 Schematic diagram of its application in human motion monitoring. DETAILED DESCRIPTION

[0055] The technical solutions in the embodiments of the present invention are described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0056] Example 1

[0057] This embodiment provides a high-performance liquid-solid self-powered sensor component, and its structural diagram is shown in Figure 1 , including upper components and lower components, wherein the upper components and lower components each include a substrate, a solid friction layer, a liquid metal, a gasket, and a wire connected to an external circuit;

[0058] The solid friction layer is a polydimethylsiloxane film with a lotus leaf microstructure;

[0059] The substrate is a polydimethylsiloxane film;

[0060] The gasket is a polydimethylsiloxane film with a hollow center;

[0061] The liquid metal serves as a liquid friction layer and an electrode.

[0062] The specific preparation method is as follows:

[0063] 1) Making upper components and lower components, the upper components and lower components are made by the same method, which is as follows:

[0064] Step 1) Preparation of a solid friction layer with two energy enhancement methods acting together

[0065] 1) Select a fresh and smooth lotus leaf surface, wipe it with alcohol, trim it into a size of about 55 mm in diameter, stick the edges tightly and place it in a plastic dish with a diameter of 60 mm; pour 13.2 g of Dow Corning 184PDMS into the plastic dish containing the lotus leaf after vacuum degassing, evacuate again for 30 min, put it in an oven at 80°C and dry it for 2 h, and peel off the lotus leaf to obtain a negative mold.

[0066] 2) The negative mold prepared in step 2) was placed in a plastic dish with a lid, and then 100 μL of chlorotrimethylsilane was dripped into the dish, and the lid of the plastic dish was immediately closed. The lid was opened after 1-2 minutes, and the chlorotrimethylsilane was evaporated at room temperature to form an anti-adhesion layer on the surface of the negative mold. 4.4 g of Dow Corning 184PDMS was evenly spin-coated on the anti-adhesion layer of the negative mold using a gel spreader at a speed of 500 rpm, and then placed in an oven at 80°C for drying for 2 hours. The dried upper film was peeled off from the surface of the negative mold to obtain a positive film with a lotus leaf microstructure.

[0067] 3) The positive mold with lotus leaf microstructure prepared in step 2) was cut into 16 squares of 1 cm x 1 cm, exposed to UVO irradiation for 1 h, and then 1 M NaOH solution was quickly sprayed on its surface so that the positive mold was covered with sodium hydroxide solution, and then left to stand for 2 h, and then the solution residue on its surface was dried to obtain a solid friction layer.

[0068] Step 2) Preparation of self-powered sensor components with two energy enhancement methods working together

[0069] 4.4 g of Dow Corning 184 PDMS was vacuum degassed and then evenly spin-coated on a glass sheet using a gel-spinning machine at 500 rpm to obtain a PDMS substrate. The PDMS substrate was placed on a heating table until it was semi-cured, and then 16 solid friction layers prepared in step 1) were laid flat on its upper surface, the solid friction layer was combined with the PDMS substrate, and then a PDMS gasket was placed on the solid friction layer (the size of the central hollow square of the PDMS gasket was 1 cm x 1 cm, the size of the outer square was 1.5 cm x 1.5 cm, and the solid friction layer was located in the central hollow square), and then dried on the heating table at 80° C. After being completely cured, it was cut into 16 separate components along the edge of the PDMS gasket, and the carrier glass sheet on the surface was removed to obtain the upper component or the lower component;

[0070] The PDMS gasket is prepared by the following method: 8.8 g of Dow Corning 184 PDMS is vacuum degassed, and then evenly spin-coated on a glass sheet at 500 rpm using a gel coater, and placed on a heating table at 80° C. for drying; then sliced ​​into blocks with an outer block size of 1.5 cm × 1.5 cm and a central hollow block size of 1 cm × 1 cm, namely the PDMS gasket.

[0071] 2) Assemble the upper and lower components together, specifically, combine the upper PDMS gasket and the lower PDMS gasket, use PDMS to bond the joint, then inject 0.4 ml of liquid metal eutectic gallium indium, lead out 2-3 cm copper wire from the injection port for connection with the external circuit, and finally use PDMS to seal the hole.

[0072] Example 2

[0073] This embodiment provides a high-performance liquid-solid self-powered sensor component, and its preparation steps and process parameters are basically the same as those of Example 1, except that: 0.2 ml of liquid metal eutectic gallium indium is injected in step 2).

[0074] Example 3

[0075] This embodiment provides a high-performance liquid-solid self-powered sensor component, and its preparation steps and process parameters are basically the same as those of Example 1, except that: 0.6 ml of liquid metal eutectic gallium indium is injected in step 2).

[0076] Example 4

[0077] The present embodiment provides a high-performance liquid-solid self-powered sensor component, and its preparation steps and process parameters are basically the same as those of Example 1, except that: when the upper component and the lower component are combined, a PDMS heightening gasket is also provided in the middle, and the heightening gasket is prepared by the following method: the PDMS gasket is prepared by the following method: 8.8g of Dow Corning 184PDMS is vacuum degassed, and then evenly spin-coated on a glass sheet at 500rpm using a gel-spinning instrument, and placed on a heating table at 80°C for drying; then sliced ​​into blocks with an outer block size of 1.5cm X 1.5cm and a central hollow block size of 1cm X1cm, which is the PDMS heightening gasket.

[0078] Example 5

[0079] The present embodiment provides a high-performance liquid-solid self-powered sensor component, and its preparation steps and process parameters are basically the same as those of Example 1, except that: when the upper component and the lower component are combined, a three-layer PDMS heightening gasket is provided in the middle, and the heightening gasket is prepared by the following method: the PDMS gasket is prepared by the following method: 8.8g of Dow Corning 184PDMS is vacuum degassed, and then evenly spin-coated on a glass sheet at 500rpm using a gel-spinning instrument, and placed on a heating table at 80°C for drying; then sliced ​​into blocks with an outer block size of 1.5cm X 1.5cm and a central hollow block size of 1cm X1cm, which is a PDMS heightening gasket.

[0080] In order to demonstrate the advantages of the technical solution provided by this application, the following is a test experiment of the high-performance liquid-solid self-powered sensor components provided by this application:

[0081] 1. Microstructure and morphology characteristics of samples

[0082] The SEM images of different templates in the solid friction layer preparation process were taken using a TM3030 scanning electron microscope (SEM) in 15kV mode. Figure 2 ;in, Figure 2 (a) is an electron micrograph of the surface of a fresh lotus leaf; (b) is an electron micrograph of a negative mold; (c) is an electron micrograph of a positive mold; (d) is an electron micrograph after ultraviolet ozone irradiation; (e) is an electron micrograph of the solid friction layer prepared in Example 1; Figure 2 In (ac), it can be observed that the present application has successfully reproduced the microscopic papillary structure on the surface of the lotus leaf, and Figure 2 It can be seen from the comparison in (de) that surface UV-ozone irradiation and alkalization treatment will not affect the morphology of the lotus leaf microstructure.

[0083] 2. Water contact angle of solid friction layer

[0084] The water contact angle change diagram of the solid friction layer is tested by an optical contact angle meter. Figure 3 ;in: Figure 3 (a) is the water contact angle of the solid friction layer without any treatment. Figure 3 (b) is the water contact angle of the solid friction layer of a single bionic lotus leaf microstructure. Figure 3 (c) is the water contact angle of the solid friction layer prepared in Example 1; it can be seen that the water contact angle of the solid friction layer with a single bionic lotus leaf microstructure is significantly higher than that of the solid friction layer without any treatment. Although the water contact angle of the solid friction layer prepared in Example 1 is lower than that of the solid friction layer with a single bionic lotus leaf microstructure, it is still higher than the water contact angle of the solid friction layer without any treatment. This proves that the solid friction layer prepared in Example 1 still has good hydrophobicity.

[0085] 3. Anti-stick performance

[0086] For a comparison of the anti-stick properties of different solid friction layers against liquid metal, see Figure 4 The experimental method is to fix a solid friction layer without any treatment on the upper pressure end surface of the universal testing machine, fix a 2.5cm x 2.5cm solid friction layer without any treatment on the lower pressure end surface of the universal testing machine, and then drip 0.5mL of liquid metal on the solid friction layer without any treatment fixed on the lower pressure end surface, control the universal testing machine to move up and down at a speed of 100mm / s, stop after 30 cycles, and use a scanning electron microscope to photograph the solid friction layer without any treatment. The results are shown in Figure 4 (a). The same method was used to test and photograph the solid friction layer of a single bionic lotus leaf microstructure. The results are shown in Figure 4 (b). According to the results, it can be observed that the liquid metal will adhere tightly to the surface of the solid friction layer without any treatment during the cyclic impact process. However, the surface hydrophobicity of the solid friction layer treated with a single bionic lotus leaf microstructure is enhanced, the roughness increases, and the surface wettability of the liquid metal decreases, showing almost no change before and after the impact, confirming that the bionic lotus leaf microstructure helps to improve the adhesion of the liquid metal on the surface of the solid friction layer.

[0087] 4. Triboelectric performance

[0088] Figure 5 To test the triboelectric performance of the linear motor at 0.5 Hz, and to measure the open circuit voltage, short circuit current and transferred charge using an electrometer, and then to compare and analyze the results, refer to Figure 5 ,in: Figure 5 (a) Comparison results of open circuit voltage of different TENGs; Figure 5 (b) Comparison results of short-circuit current of different TENGs; Figure 5(c) is the comparison result of the transferred charge of different TENGs. AUVLOS-TENG is the open circuit voltage, short circuit current and transferred charge of the self-powered sensor device prepared in Example 1. It can be seen that the open circuit voltage, short circuit current and transferred charge of the self-powered sensor device prepared in Example 1 show the same trend, and the open circuit voltage, short circuit current and transferred charge of AUVLOS-TENG are about 1-3 times higher than those of TENG prepared with other solid friction layers without any treatment (WOLOS-TENG) and TENG prepared with a solid friction layer of a single bionic lotus leaf microstructure (DLOS-TENG), which proves that the liquid-solid self-powered sensor component provided in Example 1 is very effective in improving performance.

[0089] 5. Stability and durability

[0090] The stability and durability test diagram of the liquid-solid self-powered sensor element provided in Example 1 is shown in FIG. Figure 5 , Figure 5 (a) shows the stability test results after multiple twisting, stretching and folding; Figure 5 (b) shows the results of 2000 cycles of impact durability test; the sensor exhibits excellent long-term stability and durability.

[0091] 6. Human Movement

[0092] Figure 7 In order to apply it to the collection of human motion energy; use double-sided tape to fix the AUVLOS-TENG on the desktop, connect the copper wire to one of the AC pins of the rectifier bridge on the breadboard, and the other AC pin is grounded. The other two DC pins of the rectifier bridge are connected to the positive and negative ends of the small light bulb array on the breadboard. After the circuit connection is completed, the AUVLOS-TENG is continuously tapped by the hand to produce a triboelectric effect. Within 10 seconds, the small light bulb array is successfully lit, indicating that the AUVLOS-TENG can collect human bioenergy to charge the small light bulbs. Among them: (a) is the circuit connection diagram, and (b) is the actual picture;

[0093] Figure 8 The schematic diagram of its application in human motion monitoring is shown below. The AUVLOS-TENG is connected to various parts of the human body, and the signals generated by it are collected and displayed through an electrometer. The connection to the eyelids and Adam's apple can detect blinking signals and speech signals respectively. Figure 8 (a) and (b) show that the AUVLOS-TENG can detect some weak signals by blinking or saying “hello”. Figure 8As shown in (c), AUVLOS-TENG can detect different forces, and the signal size will increase as the force increases. In addition, AUVLOS-TENG can be connected to various joints of the human body to monitor the health of human joints, such as finger joints, wrist joints, elbow joints, and knee joints. Figure 8 (dg), the signal size will change according to the different bending strengths of different joints. Some arthritis patients may not be able to bend to a certain angle, and the signal output will be correspondingly reduced. This also proves that the signal tested by the device can be used as an auxiliary basis for whether the joints are healthy. Connecting AUVLOS-TENG to the sole of the foot can detect the signals of people walking, running and jumping, such as Figure 8 As shown in (hi), the waveform and intensity of the signal will change depending on the walking method. It is expected that the device can monitor gait changes, which proves that the device has great potential in the field of gait monitoring applications.

Claims

1. A high-performance liquid-solid self-powered sensor component, characterized in that: It comprises upper components and lower components, and the upper components and lower components each comprise a substrate, a solid friction layer, liquid metal, a gasket, and a wire connected to an external circuit; The solid friction layer is a polydimethylsiloxane film with a lotus leaf microstructure; The substrate is a polydimethylsiloxane film; The gasket is a polydimethylsiloxane film with a hollow center; The liquid metal serves as a liquid friction layer and an electrode.

2. According to the high-performance liquid-solid self-powered sensor component of claim 1, a heightening gasket is further provided between the upper component and the lower component, and the heightening gasket is a polydimethylsiloxane film with a hollow center.

3. The high-performance liquid-solid self-powered sensor component according to claim 1, characterized in that: The liquid metal is eutectic gallium indium.

4. The high-performance liquid-solid self-powered sensor component according to claim 1, characterized in that: The polydimethylsiloxane is Dow Corning 184PDMS.

5. The high-performance liquid-solid self-powered sensor component according to claim 1, characterized in that: The solid friction layer is prepared by the following method: the microstructure of the surface of a fresh lotus leaf is replicated by a positive and negative molding method to obtain a polydimethylsiloxane film with a lotus leaf microstructure, the surface of the film is alkalized, and then the solid friction layer is obtained after cleaning and drying.

6. The high-performance liquid-solid self-powered sensor component according to claim 5, characterized in that: The negative mold is prepared by the following method: after vacuum degassing, polydimethylsiloxane is poured into a plastic dish with a diameter of lotus leaf, vacuumized again, placed in an oven for drying, and then the lotus leaf blade is peeled off to obtain the negative mold.

7. The high-performance liquid-solid self-powered sensor component according to claim 5, characterized in that: The specific operation of the positive mold is as follows: an anti-adhesion layer is formed on the surface of the negative mold, polydimethylsiloxane is evenly spin-coated on the anti-adhesion layer of the negative mold again, and it is placed in a 60-80°C oven for drying for 2-4 hours. The dried upper film is peeled off from the surface of the negative mold to obtain the positive film with lotus leaf microstructure.

8. The high-performance liquid-solid self-powered sensor component according to claim 5, characterized in that: The method for alkalizing the surface is as follows: exposing the positive mold with lotus leaf microstructure to an ultraviolet ozone environment for 40 minutes to 1 hour, then quickly spraying 1M NaOH solution on its surface, leaving it to stand for more than 1 hour, and drying the solution residue on its surface.

9. The method for manufacturing a high-performance liquid-solid self-powered sensor component according to claim 1, characterized in that: The steps are as follows: 1) Making upper components and lower components, the upper components and lower components are made by the same method, which is as follows: After vacuum degassing, polydimethylsiloxane is evenly spin-coated on a glass sheet carrier as a substrate. After the substrate is heated to a semi-cured state, a solid friction layer and a hollow polydimethylsiloxane gasket are sequentially placed on the surface of the substrate from bottom to top, so that the solid friction layer is combined with the substrate and the hollow polydimethylsiloxane gasket, and then dried at 60-80° C. for standby use; 2) Combine the polydimethylsiloxane gaskets of the upper and lower components, use polydimethylsiloxane to bond the joint, then inject liquid metal into the middle hollow part, lead out the wire from the injection port for connection with the external circuit, and finally use polydimethylsiloxane to seal the hole.

10. The method for manufacturing a high-performance liquid-solid self-powered sensor component according to claim 1, characterized in that: The hollow polydimethylsiloxane gasket is prepared by the following method: 1) After vacuum degassing, evenly spin-coat the polydimethylsiloxane on a glass sheet and dry it; 2) Repeat step 1) and then slice to obtain a polydimethylsiloxane gasket.